The relation between leadership styles in higher education institutions and academic staff’s job satisfaction: A meta-analysis study - Kasalak, Gamze; Güneri, Beysun; Ehtiyar, Vesile Ruya; Apaydin, Çiğdem; Türker, Gulay Özaltın (Frontiers in Psychology, 2022)
In this study, it is aimed to examine the relationship between leadership in higher education institutions [HEIs] and academic staff’s job satisfaction, which is formed by combining different leadership styles in higher education institutions, using the meta-analysis method based on correlational research. For this purpose, it was investigated whether there was a significant difference between the effect sizes of the studies investigating the relationship between leadership in HEIs and academic staff’s job satisfaction between the years 2010–2022, according to the moderator variables (leadership styles, continent, culture, and Human Development Index [HDI]). A total of 57 research data, including sample size and Pearson correlation coefficient data, were evaluated within the scope of the research. Correlational studies were calculated according to the random effect model in terms of effect direction and overall effect size; The estimated effect size value was found to be 0.374. This value shows that the overall effect size of the relationship between leadership in HEIs and academic staff’s job satisfaction is positive and moderate. However, there is no significant difference between the effect sizes of the research examining the relationship between leadership styles in HEIs and academic staff’s job satisfaction, according to continent, culture and HDI moderator variables.